KONFLIK DALAM ORGANISASI HIMPUNAN PELAJAR NAHASISWA PELALAWAN (HIPMAWAN) DI PEKANBARU - Emelda Fitria; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
HIPMAWAN is an organization of Pelalawan Student Association based in Pekanbaru City. Pelalawan student organization was established in June 1999. In the first year, Pelalawan Student Organization was hiatus because Pelalawan had just been divided into 12 (twelve) subdistricts. Later in 2000, HIPMAWAN ran the organization again. In 2007, HIPMAWAN held its 7th conference where there was a conflict during the election of the chairman of the Pelalawan student organization which resulted in the birth of a new Pelalawan student organization called IPMPB "United Pelalawan Student Association". In this study, the researcher examined what factors were driving the social conflicts; who the actors of the social conflicts were; and what efforts were taken to reduce the social conflicts. The researcher used the theory of conflict by Lewis A. Coser, with a total of 14 respondents consisting of the founders, administrators, members, and supervisors of the organization HIPMAWAN. This study used qualitative methods and the research subjects were selected using purposive sampling technique. The results of this study indicate that HIPMAWAN is now different from what it was before the 7th Congress both in the way of thinking and the unification of all members, as well as the goals of the organization. HIPMAWAN does not cover all Pelalawan students and college students, only a few. Meanwhile, some other students have formed different organizations with different names, and they have visions and missions which are certainly different. The IPMPB is a split from the 7th Congress of HIPMAWAN and was the climax of the disintegration of HIPMAWAN. Efforts to reunite the organization by the founders of HIPMAWAN have been repeatedly carried out but did not yield the expected results.Keywords: Social Conflict, Organization, Factors